Surgical Management of Camptodactyly (Sirte Journal of Medical Sciences, 2023)
Camptodactyly is a congenital deformity characterized by a flexed posture in the proximal interphalangeal joint. It is generally found in the little finger and may or may not include the other fingers. It is painless and nontraumatic [1]. It affects approximately 1% of the population. It is bilateral in around two thirds of the patients, although the degree of contracture is usually not symmetrical [2]. The deformity generally increases during growth spurts, especially during the periods of rapid growth from one to four years and from 10 to 14 years of age [3]. The primary cause of this deformity is still a matter for discussion and there is no consensus in the worldwide literature. Although some cases occur sporadically, there is often an autosomal inheritance pattern present. The metacarpophalangeal and distal interphalangeal joints are unaffected, although they may develop compensatory deformities [4].  The purpose of  this study is to assess the clinical result of surgical treatment in management of  camptadoctyly  and to evaluate the results by  clinical assessment. This retrospective study was carried out on fifteen patients. These patients with flexion deformity were admitted in Upper Limb and Reconstructive Microsurgery Unite in Assiut University Hospital and were managed by surgical treatment. Age ranges from 2to 15 year, the mean age intervention was 9.8 years.  There were 9 males and 6 females as males 60% to 40% females, there were 4 cases with positive family history and 11 case with negative family history. And 4 cases with excellent result, 4 cases good ,7 cases with fair ,17 cases with poor result. From this study the best time to operative at age between (1.5-2.5) years. Also need more family knowledge about camptodactyly to start treatment early